Management of tracheostomy during COVID-19 outbreak: Heat and moisture exchanger filter and closed suctioning system. (July 2020) - De Seta, Daniele; Carta, Filippo; Puxeddu, Roberto
Highlights: Precautions for safer management of tracheostomy should be taken for all patients. HMEFs and closed endotracheal suctioning systems protect patients and healthcare professionals. Precaution for reduce the COVID-19 diffusion should be taken until the epidemic is controlled.